Powerful Women in Leadership: An Exploration of the Characteristics of Successful Women Leaders - Singh, Kashvi (The IIE, 2018)
The objective of this study is to explore the characteristics exhibited by successful women leaders. A global concern has been identified regarding a severe underrepresentation of women occupying key leadership positions. This stems from a global perception that women lack the core competencies that are required to successfully execute the duties of a leader. Although there has been a slight improvement with regards to the number of women assuming the role of leaders, a stark disparity is still evident with limited focus being channelled towards empowering women by nurturing their skills and aiding them to realise their true potential from a leadership perspective. Research conducted on women in leadership with specific reference to their attributes is not extensive. Thus, a dire need to address this topic exists and by engaging with two prospering women leaders, an attempt was made to eradicate the concern by taking cognisance of key characteristics of women leaders among other crucial components pertaining to leadership. In-depth interviews were utilised to acquire data from participants as it facilitated extensive discussions permitting the researcher to obtain an intensive understanding of specific core aspects pertaining to the study. It was derived that women lead with a less hardened approach and that the ability to lead was a skill that was developed and enhanced over a period of time. The study addressed what embodies a successful women leader and may be utilised by women to identify these characteristics within themselves so as to enhance the number of women occupying leadership positions.
Keywords: under-representation of women; leadership positions; characteristics of women leaders; successful women leaders; perceptions